Design and creativity policy, management and practice - aJulier, Guy; aMoor, Liz (Berg Publishers, 2009)
"Does the management of design conflict with traditional ideas of creative freedom and autonomy? How do government policies and business priorities influence the day-to-day practices of designers? And how far have the processes and purpose of creative work been changed by its new centrality to business and government? Bringing together case studies and material from a range of industries and contexts, as well as a series of interviews with practitioners, Design and Creativity provides a cutting-edge account of key trends in the creative industries at the start of the 21st century. Design and other creative industries shape our lives in numerous ways, providing 'cultural' goods such as films, music and magazines, but they also shape the look and feel of everyday objects and spaces. The creative industries are important economically; and governments and businesses now make considerable efforts to manage creativity for a range of political and economic ends"--Provided by publisher.